INTEGRATED APPROACH TO OVERHEAD ANALYSIS - Y. Vorontsova; S. Chinyaeva (Вестник университета)
In article are considered two the most often used in management practice by method overheads: ABC and OVA, are allocated them opportunities, benefits and shortcomings. As the base managed with their help authors provided transactional expenses, the basic elements, and also classification of this cost type constituting them in an is conditional variable cut/constants their parts are analyzed. The directions of search problem resolutions of management of transactional costs are proposed. Authors also determined the fields of the most reasonable use of the OVA method - the analysis, the tasks solved with its help are characterized. Besides, in article ability to integrate the considered techniques for the purpose of the maximum use of their benefits in the analysis of superimposed costs.